EXPRESSION OF THE SEMANTICS OF REALITIES IN THE TRANSLATION OF ARTISTIC TEXT - Muslimakhon Rustamova (Journals Park Publishing, 2022)
The units, words and combinations of words that relate only to the domestic life, national identity, culture, social life and historical development of a certain nation are expressed in science by the term "reality". They are of special importance as they embody national and historical color. The article talks about some of the realities used in the translation of the work "Woman in the Sand" by the famous Japanese writer Abe Kobo.
Keywords: Abe Kobo